Recontracting Stability - Feldman, Allan M. (Econometrica, 1974)
[This paper contains a relatively simple proof for the stability of Edgeworthian recontracting. It also applies that proof to a random recontracting process in an economy with a finite number of utility vectors, in which the recontracting process is a Markov chain and all non-core utility vectors correspond to transient states.]